Comparison of guidelines for the management of patients with high‐risk and advanced cutaneous squamous cell carcinoma – a systematic review. (13th December 2019) - Heppt, M.V.; Steeb, T.; Berking, C.; Nast, A.
Abstract: The management of high‐risk cutaneous squamous cell carcinoma (cSCC) can be a challenge as evidence from high quality clinical trials is rare. Guideline developers are challenged to provide practical and useful guidance for clinicians even in the absence of good evidence. In order to compare treatment recommendations for high‐risk and advanced cSCC among national and international guidelines and to extract the most precise guidance provided, a systematic search was carried out in guideline databases Medline and Embase with a cutoff of 4 March 2019. Treatment recommendations for predefined clinical scenarios were extracted from selected guidelines and compared qualitatively. Five guidelines published from 2015 to 2018 were included. Excision of high‐risk tumours with margin assessment was recommended in all guidelines. A safety margin of at least 6 mm was suggested in four guidelines. There was no clear recommendation to perform a sentinel lymph node biopsy in any guideline. Lymph node dissection was uniformly recommended in the presence of nodal disease. Treatment for metastatic cSCC was poorly characterized and restricted to the use of chemotherapy and epidermal growth factor receptor inhibitors. Recommendations for the management of high‐risk and advanced cSCC were limited. We propose that guidelines should be updated to reflect recent advances in checkpoint blockade for metastatic cSCC.